Indian Soils: Characteristics, Distribution, Potentials and Constraints - Chandrakala, M.; Lakhsman, K.; Maske, Sunil P. (Chronicle of Bioresource Management, 2023)
In India due to diversity in soil forming factors and processes, various soils are found except Andisols, Spodosols and Oxisols. Though there are few Spodosols yet they are not true Spodosols. There are eight kind of soils occurring in India viz., alluvial soils (75 mha), black soils/Regur (72 m ha), red soils, laterite and lateritic soils (red and lateritic soils together occupied by 70 m ha), saline and alkali soils (10 m ha), desert soils (29 m ha), forest and hill soils (75 m ha), peaty and marshy soils. Alluvial and black soils are fertile whereas laterite, desert and alkaline soils are less fertile. There are nine key threats identified to soil include soil erosion, decline in soil organic matter (SOM), soil contamination, soil sealing, soil compaction, decline in soil biodiversity, soil salinization, landslides and desertification and also land-use change to be addressed to conserve agricultural crop lands.